A etnografia dos pedreiros livres da loja cavaleiros de Salomão - Assis, Manoel Wellington de (2011)
Freemasonry is a closed social system, comprised of free men, morality, which are started in order regardless of colour, creed and nationality. The art of Free Masons (Freemasons), relates mystically the construction of the Temple of Jerusalem, where the symbols and rituals relate to the art of building, called real art. The present study objective was to analyze the Masonic symbology and its manifestations of order sociological, philosophical and scientific. Used ethnography as methodology, which consisted in collecting right and thorough of certain symbols and language changes that speaks to him who starts, Objectifying the description of the phenomena observed in "Free Masons" and Masonic Knights of Solomon, situated in the city of João Pessoa-PB, affiliated to the Grand Orient of Paraíba. The questions were formulated with participants and compiled on the basis of a rational reflection of symbols and languages. We found that there is an Operative Masonry in Franco-contemporary Freemasonry, fuelled by symbols originating transcendental, which lay down the secrets of initiation, which in turn are linked to certain objects. Possessing a unique profile, a scientific basis which emerges from a secular thought, love and truth are focal points, followed by good and beauty, and that was created from sedimentations of knowledge that past centuries and relies on the transcendentalidade of creation.